Bridging Finance and Farming: A Literature-Based Analysis of Financial Management in Agribusiness - Mambauy, Najmah; Faisah D. Hadji Jalal; Abdani D. Bandera (Journal of Business Economics and Agribusiness, 2025)
The agribusiness sector is a cornerstone of national and global economies, encompassing the production, processing, marketing, and distribution of agricultural goods. Effective financial management within agribusiness is critical, as it directly influences resource allocation, investment decisions, risk mitigation, and overall enterprise sustainability and profitability. This study conducts a comprehensive literature-based analysis to examine how financial management practices bridge finance and farming, focusing on cost management, working capital management, financial risk management, investment appraisal, digital finance adoption, financial literacy, and corporate social responsibility (CSR). Evidence from diverse geographic and operational contexts demonstrates that structured financial practices significantly enhance profitability, operational efficiency, and resilience in the face of seasonal cash-flow fluctuations, price volatility, and environmental risks. Cost management aligns operational efficiency with strategic financial planning, while working capital management ensures liquidity and continuity during peak production periods. Financial risk management and CSR integration mitigate exposure to market and environmental uncertainties, promoting sustainable practices and stakeholder trust. The adoption of digital finance tools and platforms further strengthens the interface between financial planning and farm operations, although constraints such as low digital literacy and infrastructure limitations persist. Moreover, financial literacy among small-scale farmers emerges as a key enabler, facilitating the effective utilization of financial tools and resources. Investment decision-making frameworks incorporating scenario analysis and real-options valuation support informed capital allocation and long-term growth. Overall, the study underscores that bridging finance and farming is operationally vital, multi-dimensional, and strategically essential for achieving sustainable agribusiness growth. Insights from this analysis inform policymakers, practitioners, and researchers seeking to optimize financial management strategies in agribusiness contexts.